Frailty-associated factors among Brazilian community-dwelling elderly people: longitudinal study - Pegorari, Maycon Sousa (2019)
BACKGROUND: Frailty among elderly people is associated with negative health outcomes. Through gai-ning better understanding of this syndrome over different time periods, healthcare actions that take pre-dictive factors into consideration may be facilitated. OBJECTIVE: To identify factors associated with frailty syndrome among community-dwelling elderly pe-ople over a two-year follow-up. DESIGN AND SETTING: Longitudinal study on elderly people living in Uberaba (MG), Brazil. METHODS: Elderly individuals were selected through multiple-stage conglomerate sampling from a na-tional database. Participants were interviewed and evaluated in 2014 and again in 2016. Predictors were considered at the baseline, and frailty categories (frail, pre-frail or non-frail) at the follow-up. Frailty was identified based on the Fried criteria. Associations with socioeconomic factors, health status and physical performance were investigated using multinomial logistic regression. RESULTS: 353 individuals participated in both assessments. The final model showed that age over 80 years was predictive of both pre-frailty and frailty (odds ratio, OR 4.92; 95% confidence interval, CI: 1.57-15.38; OR 8.64; 95% CI: 2.05-36.35, respectively), while dependency regarding basic activities of daily living (OR 3.66; 95% CI: 1.22-11.02) and poor lower-limb physical performance (OR 7.87; 95% CI: 1.97-31.39) predicted frailty. A one-unit increased score for advanced activities of daily living decreased the frailty rate by 15% (OR 0.85; 95% CI: 0.74-0.99). CONCLUSION: Age over 80 years was predictive of pre-frailty and frailty, while dependency in basic acti-vities of daily living and poor physical performance predicted frailty. A one-unit increased score for advan-ced activities of daily living decreased the frailty rate by 15%.